2023
DOI: 10.3390/cancers15092596
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Therapies Targeting Bruton Tyrosine Kinase for the Treatment of Chronic Lymphocytic Leukaemia: Future Perspectives

Abstract: The development of inhibitors of Bruton tyrosine kinase (BTK) and B-cell lymphoma 2 (BCL2) has resulted in a paradigm shift in the treatment of chronic lymphocytic leukaemia (CLL) over the last decade. Observations regarding the importance of B-cell receptor signalling for the survival and proliferation of CLL cells led to the development of the first-in-class BTK inhibitor (BTKi), ibrutinib, for the treatment of CLL. Despite being better tolerated than chemoimmunotherapy, ibrutinib does have side effects, som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…8 Following this, more selective next-generation cBTKis such as acalabrutinib and zanubrutinib were developed to OncoTargets and Therapy 2024:17 [181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198] improve the efficacy and safety of ibrutinib. 9 Several phase 3 trials confirmed the superior efficacy of these cBTKis as monotherapy or in combination with an anti-CD20 mAb to CITs in the frontline and subsequent treatment settings. [10][11][12][13] Another important treatment target is an anti-apoptotic protein B-cell lymphoma 2 (BCL2), which is overexpressed in CLL cells.…”
Section: Introductionmentioning
confidence: 94%
“…8 Following this, more selective next-generation cBTKis such as acalabrutinib and zanubrutinib were developed to OncoTargets and Therapy 2024:17 [181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198] improve the efficacy and safety of ibrutinib. 9 Several phase 3 trials confirmed the superior efficacy of these cBTKis as monotherapy or in combination with an anti-CD20 mAb to CITs in the frontline and subsequent treatment settings. [10][11][12][13] Another important treatment target is an anti-apoptotic protein B-cell lymphoma 2 (BCL2), which is overexpressed in CLL cells.…”
Section: Introductionmentioning
confidence: 94%
“…DT2216 (NCT04886622), a potent B-cell CLL/lymphoma 2 (BCL-XL) degrader utilizing von Hippel-Lindau (VHL) E3 ligase recruitment, has entered Phase I clinical study for treating advanced liquid and solid tumors in 2021 78 . To date, more than 19 PROTACs are under evaluation in ongoing clinical trials, targeting POIs such as interleukin-1 receptor-associated kinase 4 (IRAK4) by degrader KT-413 79 , signal transducer and activator of transcription 3 (STAT3) by degrader KT-333 80 , and Bruton's tyrosine kinase (BTK) by degrader NX-5948 81 .…”
Section: Epigenetic Degraders In Clinical Trials and The Crystal Stru...mentioning
confidence: 99%
“…Chemotherapy and anti-CD20 mAbs therapy are the standard of care for patients with CLL ( 133 135 ). Currently, it is prominent to improve the complete remission rate and reduce chemotherapy-induced immunosuppression.…”
Section: Efficacy Of Pd-1/pd-l1 Mabs Treating Leukemia Alone or In Co...mentioning
confidence: 99%